Rural e-commerce and county economic development in China - Qin, Qiuxia; Guo, Hongdong; Shi, Xinjie; Chen, Kevin Z. (Wiley, 2023)
With the proliferation of information and communication technology in rural areas, rural e‐commerce has gradually become a new economic phenomenon in China. Using the national rural e‐commerce comprehensive demonstration policy as a quasi‐natural experiment, this study examines the causal linkage between rural e‐commerce and county‐level economic development in China. Its findings, which draw on county‐level panel data from 2011 to 2018, indicate that the policy had a positive effect on the county‐level economy in China, resulting in an overall increase in county GDP by 3.5 percent (0.7 percent annually). Our analysis further shows that the impact of the policy differed along the region and human capital dimensions. Further analysis reveals that industrial structure and nonagricultural employment were the main channels for the policy to exert a county‐level economic impact. Infrastructure improvement in China also plays an important role. The findings emphasize the importance of advancing e‐commerce in rural areas to stimulate county‐level economic development.